2009
DOI: 10.1007/s10552-009-9433-9
|View full text |Cite
|
Sign up to set email alerts
|

The association between fruit and vegetable consumption and HPV viral load in high-risk HPV-positive women with cervical intraepithelial neoplasia

Abstract: We evaluated the relationship between the dietary intake of vegetables and fruits, and the risk of cervical intraepithelial neoplasia (CIN) and determined whether these associations were modified by human papillomavirus (HPV) viral load. We enrolled 1,096 women aged 18-65 to participate in a HPV cohort study from March 2006 up to present. For this analysis, we included 328 HPV-positive women (166 controls, 90 CIN I and 72 CIN II/III). The multivariate odds ratios (ORs) and corresponding 95% confidence interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…Women 18 to 65 years of age who participated in the Korean HPV cohort study, from 2006 to the present, were included in this study; details regarding the design of the baseline measures for the cohort have been described previously (18). All study participants provided written informed consent before participation.…”
Section: Methodsmentioning
confidence: 99%
“…Women 18 to 65 years of age who participated in the Korean HPV cohort study, from 2006 to the present, were included in this study; details regarding the design of the baseline measures for the cohort have been described previously (18). All study participants provided written informed consent before participation.…”
Section: Methodsmentioning
confidence: 99%
“…Frequent consumption of fruits high in anti-oxidant nutrients was also shown to be associated with lower risk of CIN (5). Studies also support a role for fruit and vegetable consumption in reducing the risk of CIN, especially in women infected with a higher load of human papillomaviruses, the main causative factor for CIN and cervical cancer (6). A study also suggested that diets rich in plant-based nutrients may lower the risk of cervical cancer (7).…”
Section: Introductionmentioning
confidence: 97%
“…Next to human papillomavirus (HPV) [5], some behavioral factors that can be modified or avoided may play an important role in the increased risk for developing cervical cancer. Among those factors are not eating enough fruits and vegetables [6], being overweight [7], long-term use of oral contraceptives (birth control pills) [8], intrauterine device (IUD) use [9], having multiple full-term pregnancies [10], exposure to diethylstilbestrol (DES) [11], low physical activity [12], smoking [13], having multiple sexual partners [14], and human papilloma virus infection [15]. These lifestyle factors are not only important risk factors for developing cervical cancer but also impact health outcomes and quality of life [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle change can help to decrease the risk of cervical cancer to a large scale [18]. Previous studies have shown that lifestyle modifications such as eating fruits and vegetables [6], maintaining a healthy weight [7], regular physical activity [12], stopping OCP use [9], avoiding exposure to HPV and getting an HPV vaccine [15], and quitting smoking [13] may help to decrease the risk and prevent cervical cancer. Furthermore, screening behavior is considered useful for early detection in the pre-malignant phase and reduced mortality on account of cervical cancer [19].…”
Section: Introductionmentioning
confidence: 99%